S’organiser entre femmes dans l’Association internationale des travailleurs : l’expérience pionnière de la section féminine de Genève (1864-1876) - Lola Romieux (Genre & Histoire)
This article looks back at the activities of the Geneva Ladies’ Section, which later became the Women Workers’ Section, and which existed from 1868 to 1874 as a member of the International Workingmen’s Association (IWA). Created in a context where women had difficulty integrating and taking an active part in the International, the section allowed a group of women workers to participate in the militant life of Geneva. Through the development of solidarity actions (fundraising for strikers, cooperative organization, children’s festivities) and by taking a stand in favor of women’s work, the women activists succeeded in having an impact on the IWA even beyond Swiss borders. The recognition and the fame obtained allowed the propagation of a new model of workers’ organization: the women’s section, aiming for the integration of the demands of women workers with those of the male workers.